PERTUMBUHAN Chlorella spp. DALAM MEDIUM EKSTRAK TAUGE (MET) DENGAN VARIASI pH AWAL - Prihantini, Nining Betawati; Putri, Berta; Ratna, Ratna (UI Scholars Hub, 2023)
The Growth of Chlorella spp. in Tauge Extract Medium (TEM) with Various Initial pH. Research on the effect of tauge extract medium initial pH value on Chlorella Beijerinck cell densities at peak condition had been done. The research was an experimental study with complete random design with 5 treatments (tauge extract medium with initial pH 5,6,7,8, and 9). At peak condition the highest cell density (5.677.625 sel/ml) was occured in medium with initial pH 7 and the lowest (3.374.100 sel/ml) in medium with initial pH 5. Anova test shown that there was an effect (p value>0,05) of tauge extract medium initial pH value on Chlorella cell densities (cell/ml) at peak condition. Multiple comparison test showed that mean of cell numbers of Chlorella differed among treatments (p value>0,05) except between media with initial pH 8 and 9.